2021
DOI: 10.3390/toxics9120338
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Exposure to Ambient Air Pollution among Late-Onset Preeclamptic Cases Is Associated with Placental DNA Hypomethylation of Specific Genes and Slower Placental Maturation

Abstract: Exposure to ambient air pollution during pregnancy has been associated with an increased risk of preeclampsia (PE). Some suggested mechanisms behind this association are changes in placental DNA methylation and gene expression. The objective of this study was to identify how early pregnancy exposure to ambient nitrogen oxides (NOx) among PE cases and normotensive controls influence DNA methylation (EPIC array) and gene expression (RNA-seq). The study included placentas from 111 women (29 PE cases/82 controls) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…These toxicants also cause alterations in the placenta’s DNA. Early pregnancy exposure to NO x changed the placental DNA methylation leading to placental immaturity ( 54 , 55 ). Chronic interaction with NO x is also linked with diabetes mellitus.…”
Section: Endocrine Disruptive Effects Of Gaseous Constituents Of Smogmentioning
confidence: 99%
See 1 more Smart Citation
“…These toxicants also cause alterations in the placenta’s DNA. Early pregnancy exposure to NO x changed the placental DNA methylation leading to placental immaturity ( 54 , 55 ). Chronic interaction with NO x is also linked with diabetes mellitus.…”
Section: Endocrine Disruptive Effects Of Gaseous Constituents Of Smogmentioning
confidence: 99%
“…Moreover, other studies have revealed that the chronic exposure to air pollution may produce alterations in normal ovarian function e.g., estrogen-like effect or gene mutation, which can lead to ovarian cancer ( 66 ). Additionally, transplacental exposure to PM is connected to higher placental mutation rate and such epigenetic alterations may be a reason for placental carcinogenicity ( 55 ).…”
Section: Endocrine Disrupting Effects Of Particulate Matter (Pm ...mentioning
confidence: 99%
“…17 One mechanism involved in fetal programming may be epigenetic changes, 7,8 which have been reported in placentas exposed to ambient air pollution and in placentas from women who live on farms. 18,19 Differences in cord blood cytokines and immune cells have also been found between neonates who later develop an allergic disease and healthy controls. For example, detectable levels of interleukin 4 and interferonγ in cord blood were associated with reduced incidences of asthma and atopy during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Another well‐studied prenatal exposure linked to an increased risk of atopic disorders in offspring, particularly wheezing and asthma, is maternal smoking during pregnancy 17 . One mechanism involved in fetal programming may be epigenetic changes, 7,8 which have been reported in placentas exposed to ambient air pollution and in placentas from women who live on farms 18,19 . Differences in cord blood cytokines and immune cells have also been found between neonates who later develop an allergic disease and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alterations in placental DNA methylation of the LINE-1 and HSD11B2 genes might be involved in PM10-induced reproductive and developmental toxicity [ 28 ]. Furthermore, NO 2 exposure during early pregnancy influenced placental DNA methylation in preeclampsia and resulted in placental immaturity and sexual dimorphism [ 29 ]. In addition, the researcher found that the epigenetic modifiers such as TET2 and TET3 were upregulated in the placenta of patients with spontaneous abortion [ 30 ].…”
Section: Introductionmentioning
confidence: 99%